Evaluation of Different Front Surface Passivation Schemes for p-type IBC Solar Cells - Meßmer, Marius; Rachdi, Lazhar; Saint-Cast, Pierre; Schmidt, Stefan; Jung, Nico; Lossen, Jan; Wolf, Andreas (SiliconPV Conference Proceedings, 2025)
In this work, we investigate different front-side passivation approaches for p-type IBC solar cells. We compare a POCl3-diffused and SiNx-passivated front floating emitter (FFE) with an undiffused front surface passivated by a layer stack of aluminum oxide Al2O3 and silicon nitride SiNx, using different technologies for Al2O3 deposition. Further, we investigate a boron-doped front surface field (FSF), realized with different BBr3 diffusion approaches. We achieve promising implied open-circuit voltages iVoc of up to 740 mV with Al2O3/SiNx-passivation, which is a 7 mV increase compared to the reference process using the phosphorus-doped FFE. Further, we fabricated boron-doped FSF samples exhibiting promising recombination parameters of j0 < 6 fA/cm2. The transfer of the Al2O3/SiNx-passivation into pIBC solar cells already reaches peak efficiencies of h = 23.3%, comparable to the FFE.